2021
DOI: 10.3390/en14051305
|View full text |Cite
|
Sign up to set email alerts
|

Fault Detection and Diagnosis Methods for Fluid Power Pitch System Components—A Review

Abstract: Wind turbines have become a significant part of the global power production and are still increasing in capacity. Pitch systems are an important part of modern wind turbines where they are used to apply aerodynamic braking for power regulation and emergency shutdowns. Studies have shown that the pitch system is responsible for up to 20% of the total down time of a wind turbine. Reducing the down time is an important factor for decreasing the total cost of energy of wind energy in order to make wind energy more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Most of the time, the pitch of an audio signal is used to describe the vibration of a frequency. Many researcher can say that a high frequency audio wave has a high pitch, and a low frequency audio wave has a low pitch [37]. librosa.piptrack figures out how high or low the sound files are.…”
Section: ) Pitchmentioning
confidence: 99%
“…Most of the time, the pitch of an audio signal is used to describe the vibration of a frequency. Many researcher can say that a high frequency audio wave has a high pitch, and a low frequency audio wave has a low pitch [37]. librosa.piptrack figures out how high or low the sound files are.…”
Section: ) Pitchmentioning
confidence: 99%
“…The yawing system regulates the yaw angle γ to align the turbine rotor with the wind direction to maximize power, to place the rotor out of the wind in storm conditions or to resolve cable twist in the tower. Pitch and yaw systems can also be hydraulically actuated instead of using an electric drive [142,143].…”
Section: Pitch and Yaw Systemsmentioning
confidence: 99%
“…It is however also interesting to detect subtler failures, where a pitch system component sees its functionality degraded in a way that may impact turbine operation in the longer term without necessarily prompting an immediate reaction from the safety system, i.e., the pitch system still tracks the reference cylinder position, but its operational envelope is reduced, so it cannot handle wind conditions well within its design specifications. The potential benefits of a system capable of such detection are evident, and they have long elicited ample research, as shown by the detailed and current review of the literature provided by Asmussen et al [32], who point out that realistic methods able to cope with the stochastic nature of wind turbine behavior are yet to be developed (hence, this paper).…”
Section: Introductionmentioning
confidence: 99%